Effects of m-nifedipine and nifedipine given intraduodenally on coronary flow, myocardial oxygen, and carbon dioxide metrabolism in dogs - MR Rao; QY Liu; SL Jia (Acta Pharmacologica Sinica, 2017)
Effects of m-nifedipine and nifedipine given intraduodenally on coronary flow, myocardial oxygen, and carbon dioxide metrabolism in dogs